Chromatin nanoscale compaction in live cells visualized by acceptor‐to‐donor ratio corrected Förster resonance energy transfer between DNA dyes. Issue 12 (21st August 2019) - Pelicci, Simone; Diaspro, Alberto; Lanzanò, Luca
Abstract: @Chromatin nanoscale architecture in live cells can be studied by Förster resonance energy transfer (FRET) between fluorescently labeled chromatin components, such as histones. A higher degree of nanoscale compaction is detected as a higher FRET level, since this corresponds to a higher degree of proximity between donor and acceptor molecules. However, in such a system, the stoichiometry of the donors and acceptors engaged in the FRET process is not well defined and, in principle, FRET variations could be caused by variations in the acceptor‐to‐donor ratio rather than distance. Here, to get a FRET level independent of the acceptor‐to‐donor ratio, we combine fluorescence lifetime imaging detection of FRET with a normalization of the FRET level to a pixel‐wise estimation of the acceptor‐to‐donor ratio. We use this method to study FRET between two DNA binding dyes staining the nuclei of live cells. We show that this acceptor‐to‐donor ratio corrected FRET imaging reveals variations of nanoscale compaction in different chromatin environments. As an application, we monitor the rearrangement of chromatin in response to laser‐induced microirradiation and reveal that DNA is rapidly decompacted, at the nanoscale, in response to DNA damage induction. Abstract : Fluorescence lifetime imaging (FLIM) detection of Förster resonance energy transfer (FRET) can be used to measure nanoscale chromatin compaction in live cells. However, the measured FRET level can be affected by the relative amount of acceptor and donor molecules. This work introduces a novel method to correct the FRET level for variations of the acceptor‐to‐donor ratio. The results show consistent spatial maps of nanoscale chromatin compaction in live cells.